Implementation of a community-based exercise program for Parkinson patients: using boxing as an example - Domingos, Josefa (2022)
Background: Persons with Parkinson’s disease (PD) benefit from continuous exercise through participation in community-based exercise programs. However, community programs often lack PD-specific knowledge needed to provide safe and adequately dosed exercise.